PENGARUH PENDEKATAN CHEMO-ENTREPRENEURSHIP ( CEP) TERHADAP MINAT DAN HASIL BELAJAR SISWA SMA N 1 BUKIT KABUPATEN BENER MERIAH PADA MATERI PERUBAHAN MATERI - Sri Ismulyati; Yudi Ikhwani (Lantanida Journal, 2018)
The aim of this research was to increase the entrepreneurship interest and student learning result of chemistry learning process, The innovation and renewal in Chemo-Entrepreneurship (CEP) approach which is related to real objects (contextual) were needed so that the children were motivated and interested to learn chemistry. This research was implemented by IPA-2 students of SMAN I Bukit school that Bener Meriah District. The sample of this research was about 25 students. The research design used was the Class Action Research (PTK) which consists of planning, action, observation and reflection. Data collection techniques in this study were obtained by observation, pre test, post test, and questionnaire. The result of this research for the students' learning outcomes in the 1st cycle was showing that the student learning completeness about 36% with an average value about 63.77%, and in the 2nd cycle was obtained about being 84% complete value with an average value about 82.7%. Based on the result showing that the success of students increased in the 2nd cycle and student responses positively about 83.2%. The interest of the students of entrepreneurship interest was increased from 20% in 1st cycle to 47% in 2nd cycle and it turned out students who stated positively about 83.2% the student interest increased from I to cycle II i.e. 20% to 70%. Based on the results of this study can be concluded that the interest and learning outcomes were increased by the influence of CEP approaches.